A Structured Approach for Investigating the Causes of Medical Device Adverse Events. (27th November 2014) - Amoore, John N.
Abstract : Aim . Medical device-related adverse events are often ascribed to "device" or "operator" failure although there are more complex causes. A structured approach, viewing the device in its clinical context, is developed to assist in-depth investigations of the causes. Method . Medical device applications involve devices, clinical teams, patients, and supporting infrastructure. The literature was explored for investigations and approaches to investigations, particularly structured approaches. From this a conceptual framework of causes was developed based primarily on device and clinical team caring for the patient within a supporting infrastructure, each aspect having detailed subdivisions. The approach was applied to incidents from the literature and an anonymous incident database. Results . The approach identified and classified the underlying causes of incidents described in the literature, exploring the details of "device, " "operator, " or "infrastructure" failures. Applied to incident databases it suggested that causes differ between device types and identified the causes of device unavailability. Discussion . The structured approach enables digging deeper to uncover the wider causes rather than ascribing to device or user fault. It can assess global patterns of causes. It can help develop consistent terminology for describing and sharing information on the causes of medical device adverse events.